THE ANALYSIS OF NURSING CARE DOCUMENTATION IN OUTPATIENT UNITS - Any Kurniawati; Agustin Indracahyani; Aat Yatnikasari (International Journal of Nursing and Health Services (IJNHS), 2019)
Outpatient units have high activity and interaction, which increases the risk of neglecting full documentation of nursing care. This study aims to analyze factors contributing to the lack of optimal documentation of nursing care in an outpatient unit. This study employed a fish bone analysis approach to identify the root of problems of documenting nursing care in an outpatient unit. This research was conducted in an outpatient unit of the Children's and Mother's Hospital in Jakarta. The data collection techniques of this study were questionnaires, observations, and interviews with the head of the room, Clinical Instructors, implementing nurses, Case Managers, and Nursing Fields. The analysis reveals several results. Nurses, clinical instructors, activities in high work environments, as well as policies and tools for assessment and supervision are inadequate. The absence of effective systems and mechanisms for supervising nursing care documentation and manual documentation systems contributes to the lack of optimal documentation of nursing care in the outpatient unit. Documentation of nursing care extremely depends on the workforce, work climate, sets of policies, systems, and facilities. This study recommends programs and supervision activities for outpatient nursing care documentation performed by the Nursing Division, head of rooms, and Clinical Instructors, arranges supervision tools, arranges patients’ effective and efficient assessment documentation according to accreditation, policy re-socialization and documentation techniques, as well as energy management and implementation time documentation of nursing care in an outpatient unit. Keywords: clinical instructors, an outpatient unit, nursing care, nursing documentation, supervision nursing care documentation.